Penerapan E-LKPD Berbasis Cirebon Local Wisdom pada Materi Globalisasi terhadap Kemampuan Berpikir Kritis Siswa Kelas VI SD - Fitriyani Fitriyani; Eko Handoyo; Erni Suharini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the lack of innovation in learning in interactive assessments based on Cirebon local wisdom. The integration of Cirebon local wisdom is important as a learning resource that makes the material more relevant to students' daily lives. This study aims to describe the process of implementing E-LKPD based on Cirebon Local Wisdom in globalization material and its effectiveness in improving students' critical thinking skills. The research method used is mixed methods with a concurrent embedded model. The research subjects were 13 sixth-grade students. The research instruments used were pretest-posttest sheets and observation sheets. The data analysis used descriptive statistics and N-Gain through SPSS. The results showed that students' critical thinking skills increased from a pretest score of 58.46 to a posttest score of 88.72 with a learning completeness percentage of 84.62%. The N-Gain result was 0.76 (≥ 0.70) with a high category. Based on these research results, it was concluded that the application of E-LKPD based on Cirebon Local Wisdom created more meaningful and effective learning, thereby significantly improving students' critical thinking skills.